Code of Silence (The Dance Current, 2017)
Fifteen years ago, Lisa, a dance conservatory student, became pregnant. She was told in no uncertain terms by her school’s directors that abortion was recommended, and that she wouldn’t be allowed to continue attending the conservatory otherwise. It was made clear to her that the fact that her pregnancy would be in its seventh month at the time of graduation...